Woman's Work in the Service of Empire: Lady Margaret Field (1905–94) from School Teacher to Governor's Wife. Issue 3 (4th May 2018) - Constantine, Stephen
ABSTRACT: The presence of single and also of married British women in overseas colonies, especially those employed by or married to men in the Colonial Service in the later colonial period, has been the subject of scholarly enquiry. Their lives, roles and values and their distinctive contribution, if any, to the development of empire and of its ending have been debated. Their gendered roles were usually subordinate in a masculine culture of empire, and especially as wives they are commonly regarded as marginalised. The archived records left by Lady Margaret Field reveal her commitment as a single woman to a colonial mission and her sense of achievement as a school teacher and educational administrator, while also acknowledging the independence and career satisfactions she subsequently lost when she married a senior Colonial Service officer who rose to be a governor. But it is also apparent that, though incorporated and subordinate as a governor's wife to her husband's career, she was not marginalised to a separate sphere. As is evident from this case study, governors' wives had important and demanding political duties, and such responsibilities need to be acknowledged.